Análisis comparativo del impuesto de renta y del impuesto sobre la renta para la Equidad CREE (2014)
In the present work a comparative analysis of degree of Supplemental Income tax and opposite the new Income Tax for Equity CREE, enshrined in law in 2012 and 1607 apply from January 1, 2013 was performed. The purpose of present study lies in the importance of giving out detailed regulations of the new tax; compared to the existing tax from income, in order to show a broader picture of the above to the general taxation and particularly to those who have or want to form a corporation form and who are required to declare Income Tax and the Complementary and Income Tax for Equity CREE. The development of this comparative analysis described in degree work presented, it was possible to information collected by sources concerning the documents which is regulated country tax legislation framed in constitutional tax laws; Also, texts, documents and web pages with information about the tax issue, mainly income tax and complementary, as the new Income Tax for Equity CREE.